The importance of training family physicians in promoting physical activity and sports - STEFANET, Gheorghe; JUCOV, Artiom; TABIRTA, Alisa; CEBANU, Serghei (One Health & Risk Management, 2025)
Introduction. Training family doctors in promoting physical activities and assisting individuals engaged in sports can significantly contribute to the primary prevention of non-communicable diseases. However, current training in this field, both in university and postgraduate programs, is often insufficient or even absent. The study aims to improve training programs for family physicians in the field of promoting physical activities by developing a model of continuing education program for them. Material and methods. A bibliographic study was conducted on the importance of training family physicians in promoting physical activity and sports. The study utilized the PubMed/MEDLINE, Google Scholar, and ResearchGate databases, covering the period from 2004 to 2024, using the following keywords: physical activity promotion, sports medicine, prevention, training, and family medicine. Results. In Moldova’s medical education system, it is crucial to implement educational interventions that integrate topics from sports medicine and physical activity promotion into undergraduate and postgraduate training. Our recommendations focus on developing appropriate curricula, providing continuing education sessions, and establishing partnerships with experts in sports medicine. Consequently, we propose a project for designing a training program for family physicians to enhance their role in promoting physical activity and sports. Conclusions. To effectively promote physical activities and support individuals engaged in sports, it is essential to develop and implement continuous training programs for family doctors, tailored to local needs and resources.